Just as I am : the autobiography of Billy Graham - Graham, Billy (HarperSanFrancisco/Zondervan, 1997)
One of the world's most beloved and respected leaders tells his inspiring life story in a momentous work of faith and insight. Billy Graham is truly the world's pastor -- "the man who has preached to more people than any human being who has ever lived" (Time). In five decades Graham has led his ministry around the globe, speaking in person to more than 200 million people. Yet his message has remained singular and strong, as Graham continually implores his audience to "choose Christ, as I did." Even more notable is that, unlike many of his counterparts, Graham has maintained a noble reputation of integrity with no trace of scandal. At 77, Graham now looks back on an incredible lifetime of personal relationships, whirlwind activity, ministry, leadership and influence. In a warm, unassuming voice, he shares the stories of his beginnings in the Church, and the overwhelming success he has achieved speaking the word of God as an Evangelist. He describes the tolls this success took on his family -- and credits his remarkable wife, Ruth, for their tremendous accomplishments together. Graham speaks of his embarrassing beginnings with fellow Baptist Harry S Truman, and friendships and associations with every U.S. president since Eisenhower, including anecdotes of lunch with Hillary Clinton and the behind-the-scenes drama of Nixon's rise and fall from power. In Just As I Am, Billy Graham shares how he came from ordinary beginnings to have an extraordinary life of prestige and influence -- all derived from his unshakable belief in Christ. Graham says, "As I look back over the years ... my deepest feeling is one of overwhelming gratitude. I cannot take credit for whatever God has chosen to accomplish through us; only God deserves the Glory ..."
card
Keywords: Graham, Billy -- autobiography; Christian evangelists -- Biography